(3cJGFH CYdGe GdCNHGQ ef abgGA ePgH GdfYeGf GdeNJGQs - (3Gdcahj , eMehO Hf SdjeGf GdMfaj GdQhej,J (B990 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CQSd QShdg HGdgOi hOjf GdMb s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B168s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B434 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B207 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1472s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(2949) s
Keywords: (3GdJGQjNs